Utility of exhaled nitric oxide in pediatric practice-review of literature. - Arnaudova Danevska, Ivana; Balkanov, Trajan; Boskovska, Katerina; Jakjovska, Tatjana; Popova, Gorica; Cakalarovska, Irena (Macedonian Association of Anatomists and Morphologists, 2019)
The field of interest for measurement of exhaled nitric oxide (NO) and nasal NO is significantly evolving over the last 25 years, with over 1000 publications published in that area. Inflammation of the airways is a central process in asthma and other lung disorders, but the monitoring of the inflammation has not been included in the current recommendations. The exhaled air contains volatile media such as nitric monoxide, carbon monoxide, ethane, pentane and non-volatile substances in the liquid phase in the exhalation, as a condensate (hydrogen peroxide). It is increasingly confirmed that the measurement of exhaled mediators in general, and especially NO, is a new way to monitor certain aspects of asthma, COPD and interstitial lung disease, which cannot be estimated with other methods, like lung function. In asthma, exhaled NO is recommended to be used as a marker for diagnosis, for monitoring the response of anti-inflammatory drugs, confirming the safety of therapy and predicting asthma exacerbation. Measurements of FeNO are easily performed, they are reproducible and technically less expensive than the analysis of induced sputum. In symptomatic patients, high FeNO levels (> 50 ppb), refer to significant eosinophilia in the airways, which will most likely respond to treatment with ICS. The current data provides support for the diagnostic use of FeNO in children with symptoms of asthma. For patients with chronic and/or severe asthma, FeNO levels are useful for determining whether eosinophilic inflammation of the airways is active or not. Both high (> 50ppb) and low (<25 ppb) levels of FeNO can be used to for predicting the outcome in patients with a definitive history of asthma who are currently in remission and who have stopped treatment with ICS.
Keywords: asthma; children; exhaled nitric oxide; recommendations